Pengembangan Aplikasi Mobile untuk Pembelajaran Bahasa Arab dengan Pendekatan Kontekstual - Moh. Zulkifli Paputungan; Mohammad Ahsanuddin; M. Kholis Amrullah; Sepriadi (Faculty of Education and Teacher Training, 2024)
This research focuses on developing a mobile application for Arabic language learning using a contextual approach, designed for eighth-grade students. The Research and Development (R&D) methodology with the ADDIE model was implemented, encompassing stages of needs analysis, design, development, implementation, and application evaluation. The validation process involved media and material experts, resulting in a highly favorable assessment with average scores of 94.4% for technical aspects and 95.2% for curriculum alignment. The application's implementation actively engaged teachers and students, generating very positive responses. The app was deemed user-friendly, relevant to learning needs, and effective in enhancing students' motivation and understanding of Arabic language materials. The final evaluation phase identified several areas for improvement, which were then integrated to refine the application, enhancing its support for contextual and interactive learning. The significance of this research lies in its contribution to educational technology development, particularly in the domain of Arabic language learning. The findings demonstrate great potential for wider adoption in other educational institutions. The contextual approach implemented in this mobile application offers an innovative solution to improve effectiveness and engagement in Arabic language learning, aligning with the trends of education digitalization and the need for more adaptive and personalized learning methods.